(untitled) (Archives of Clinical Psychiatry, 2019)
Background: Increasing evidence supports an association between psychological well-being and overall health, however, much remains to be understood about this association. Objectives: The current study addresses this issue by presenting a new perspective focusing on health perceptions. Additionally, it examines the impact of each of six dimensions of psychological well-being on health perception. Methods: Data for this study were collected from a sample of 1,155 Portuguese adults in various settings. Results: Findings reveal that psychological well-being dimensions' impact differently on prior, current, and health outlookperceptions. Furthermore, the dimension depressed mood influences current health perception; in turn, current health perception is the strongest predictor for psychological well-being. Discussion: Our results provide support for a bidirectional relationship between health perception and psychological well-being.